Advanced exergy analyses and optimization of a cogeneration system for ceramic industry by considering endogenous, exogenous, avoidable and unavoidable exergies under different environmental conditions. (April 2021) - Caglayan, Hasan; Caliskan, Hakan
Abstract: In this study, the conventional and advanced exergy analyses are performed to the cogeneration system (COGEN) that consists of gas turbine unit and spray dryers in ceramic factory under five different environment conditions for the optimization. According to exergy analysis, the maximum exergy efficiency of the COGEN is found as 29.850% at 30 °C environment temperature, while the maximum exergy destruction rate is calculated as 17810.61 kW at 30 °C environment temperature. According to advanced exergy analysis, combustion chamber (CC) may not be the only component to be focused on for exergy destruction. Because, the exergy destruction rate can be caused by its own internal reasons (endogenous) as well as other components (exogenous). In other words, the relationship between components can be revealed. Chemical reactions occurring in CC, wall tile dryer (WD) and ground tile dryer (GD) cause an increase in endogenous exergy destruction rate of the COGEN system. Due to the improvement potential increase in components, the exergy efficiency of the whole system (COGEN) increases to between 45% and 47% with an increase of approximately between 15% and 17% for five different dead temperatures. Also, the unavoidable exergy destruction rates of the CC and air compressor (AC) are much higher than their avoidable exergy destruction rates. In particular, the avoidable exergy destruction of the WD and GD has been shown to have a significant effect on other components. Highlights: Advanced exergy analysis and optimization of a cogeneration system for ceramic industry as first in literature. Definition of new exergy parameters for a cogeneration system. Effects of environmental temperatures on the efficiencies of the system and components.